2021
DOI: 10.1002/jsp2.1151
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of in vivo three‐dimensional changes of the spinal canal after corrective surgeries of the idiopathic scoliosis

Abstract: Objective To determine the three‐dimensional (3D) changes of the spinal canal length (SCL) after corrective surgeries and their association with the radiographic and clinical outcomes of idiopathic scoliosis patients. The length of the spinal cord has been demonstrated to be strongly correlated with the SCL. Understanding the changes in SCL could help determine the morphologic changes in the spinal cord to prevent spinal cord injury. Methods Twenty‐seven scoliotic patients' 3D spinal canal were investigated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(80 reference statements)
0
0
1
Order By: Relevance
“…Based on our review of the literature, we know that the results of animal experiments (the maximum tensile length and proportion that the spinal cord can withstand) do not apply to humans due to species differences. Additionally, in the previous study ( 29 ), due to different measurement methods, the results in the current study were larger than those reported in the literature.…”
Section: Discussioncontrasting
confidence: 87%
“…Based on our review of the literature, we know that the results of animal experiments (the maximum tensile length and proportion that the spinal cord can withstand) do not apply to humans due to species differences. Additionally, in the previous study ( 29 ), due to different measurement methods, the results in the current study were larger than those reported in the literature.…”
Section: Discussioncontrasting
confidence: 87%